The Impact of Job Satisfaction on Financial Performance in Jordanian Industrial Companies: The Mediating Role of Innovation - Al Hayek, Mohammad Ali; E’leimat, Dheifallah; Alshdaifat, Sajead Mowafaq; Mansour, Israa Jawdat (International Review of Management and Marketing, 2025)
This study looks at the relationship between job satisfaction, innovation and financial performance in Jordanian industrial companies with innovation as a mediating variable. Based on Resource-Based Theory and Innovation Theory, the study assumes that job satisfaction leads to innovation which in turn leads to financial performance. A quantitative research methodology was used and data was collected from 159 financial professionals from 33 publicly listed companies on the Amman Stock Exchange. A structured survey was administered to economic and accounting professionals and Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis. The findings show a strong positive relationship between job satisfaction and innovation, the employees are the driving force behind innovation. However, there is no direct relationship between job satisfaction and financial performance. Instead, the results show that innovation is a mediator between job satisfaction and financial performance, it’s the key to translate employee satisfaction into financial success. These results highlight the need to have a work environment that prioritizes employee satisfaction and innovation to enhance organizational competitiveness and financial outcomes.